Research of CNC Gear Hobbing Automatic Programming Technology - Diao Xiuhui; Li Jinbo (Jixie chuandong)
In order to improve the efficiency of gearprocessing,a kind of CNC hobbing automatic programming system is presented. Firstly,the mathematical model of the hober- axial roll cut method is established.Then,the hober hardware platform of CNC gear hobbing automatic programming system is established,the several functional modules and the software page set are designed. Finally,the object- oriented software programming technology,communications technology,multi- threading technology and decoding technology in the system development are analyzed. The automatic programming technology provides some convenient reference and experience for the future gear hobbing CNC machining.